Self-sampling for oropharyngeal and rectal specimens to screen for sexually transmitted infections: acceptability among men who have sex with men. Issue 1 (15th August 2008) - Wayal, S; Llewellyn, C; Smith, H; Hankins, M; Phillips, A; Richardson, D; Fisher, M
Abstract : Objectives: To explore the feasibility and acceptability of self-sampling for oropharyngeal and rectal specimens to screen for sexually transmitted infections (STIs) among men who have sex with men (MSM). Participant's willingness to self-sample at home was also explored. Methods: Participants of a study to evaluate the sensitivity and specificity of self versus nurse taken oropharyngeal and rectal specimens were surveyed to assess the feasibility and acceptability of self-sampling using specimen collection methods (gargle, OraSure mouth pad to collect oropharyngeal specimens and APTIMA unisex swabs to collect rectal and pharyngeal specimens). Acceptability was measured using a five-point Likert-type response scale (for example, 1 =  strongly disagree; 5 =  strongly agree). Open-ended questions explored participants' experiences of self-sampling. Results: Of 334 eligible MSM, 301 (90%) participated in the study. Altogether, 301 participants self-sampled using gargle and rectal and pharyngeal swabs and 288 using mouth pad. Complete questionnaire data from 274 participants showed that feasibility and acceptability of self-sampling using gargle and mouth pad was higher (92%) than pharyngeal swabs (76%). Rectal swabs were acceptable to 82% participants. Despite some discomfort and difficulty in using swabs, 76% were willing to use all four methods for self-sampling in the future. Home sampling was acceptable (84%) as it was perceived to be less intrusive and more convenient than a clinic visit and likely to reduce genitourinary medicine (GUM) waiting time. Conclusions: Self-sampling for rectal and oropharyngeal specimens is feasible and acceptable to MSM. Self-sampling can be offered as an alternative to clinic-based testing and has the potential to improve choice, access and uptake of screening for STIs.